Ta’awun based muhammadiyah solidarity buying To support the economy resilient of street vendors during covid-19 period in north lampung - Prihatmojo, Agung; Badawi, Badawi; Nugroho, Purna Bayu (Universitas Trunojoyo Madura, 2021)
The purpose of this study was to determine the impact of solidarity buying on the economic resilience of street vendors' families during the Covid-19 pandemic. This study uses a qualitative research method with a descriptive approach. Determination of the subject using purposive to be determined according to the purpose of the study. The subjects in this study amounted to 5 street vendors in Kotabumi, North Lampung. The technique of collecting data is semi-structured interview. Data analysis technique with steps of data reduction, data presentation, and verification. Testing the validity of the data using data triangulation. The results of the ta'awun-based Solidarity buying research were able to increase the income of street vendors during the pandemic. The income of street vendors can increase not only from the profit of buying and selling but from the ta'awun of buyers who often overspend or give alms. Ta'awun really helps street vendors in setting aside money to pay debts. Ta'awun Muhammadiyah activities in North Lampung during the pandemic also helped fulfill the food needs of street vendors, namely the distribution of free basic-necessities to street vendors.